(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This study focuses on enhancing the accounting and control systems within budget organizations to boost the efficiency of budget fund utilization. In today’s dynamic economic environment, effective management of budgetary resources has become crucial for public and private sector organizations alike. The research examines existing accounting practices, identifies inefficiencies, and proposes methodologies for optimizing resource allocation and monitoring expenditures. Key elements include the implementation of advanced accounting software, regular audits, and the establishment of clear financial protocols.